2013
DOI: 10.1177/1096348012471376
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Customer Satisfaction, Delight, and Loyalty in the Hospitality Industry

Abstract: Customer satisfaction has been a focus of researchers and marketers as an important antecedent of customer loyalty. Some recent studies propose that customer delight possibly produces greater customer loyalty than satisfaction. Loyalty has also become of greater interest to researchers and marketers as a multiphase concept as well as a useful segmentation of customers with accompanying targeted strategies. As one of few empirical studies on customer satisfaction, delight, and loyalty, the primary objectives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
184
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(201 citation statements)
references
References 123 publications
(235 reference statements)
7
184
0
10
Order By: Relevance
“…Customer delight is defined as a customer's reaction to experiencing a product or service that provides an unanticipated level of value or satisfaction (Chandler, 1989). Based on this conceptualization, customer delight is related to, but distinct from, customer satisfaction, particularly in respect of its effect on customer loyalty (Hicks, Page, Behe, Dennis, & Fernandez, 2005;Kim & Mattila, 2013;Kim, Vogt, & Knutson, 2013;Loureiro, 2010;Oliver, 1997). Scholars such as Ma et al (2013) and Crotts and Magnini (2011) have stated that customer delight is new to the literature, arguing that this necessitates further research into its relationship with other concepts such as satisfaction and loyalty.…”
Section: Introductionmentioning
confidence: 92%
“…Customer delight is defined as a customer's reaction to experiencing a product or service that provides an unanticipated level of value or satisfaction (Chandler, 1989). Based on this conceptualization, customer delight is related to, but distinct from, customer satisfaction, particularly in respect of its effect on customer loyalty (Hicks, Page, Behe, Dennis, & Fernandez, 2005;Kim & Mattila, 2013;Kim, Vogt, & Knutson, 2013;Loureiro, 2010;Oliver, 1997). Scholars such as Ma et al (2013) and Crotts and Magnini (2011) have stated that customer delight is new to the literature, arguing that this necessitates further research into its relationship with other concepts such as satisfaction and loyalty.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, loyalty programs should be carefully planned, evaluated, and constantly developed based on a long-term relationship with customers that can elevate customer loyalty (Blackwell, Miniard, & Engel, 2005;Choi & Chu, 2001;Mattila, 2006;O'Brien & Jones, 1995). To ensure that loyalty programs are attractive to customers and differentiated from the competing firms, loyalty programs can add more personal and subjective-oriented benefits such as feeling been entertained, honored, and delighted by "wowing" customers, which can produce emotional and interpersonal bonds between customers and a company, product, or service and the bonds can provide an important psychological value to the customers (Berman, 2006;Kim et al, 2013;Mattila, 2006). These emotional benefits can be perceived as more valuable to the customers than monetary rewards or extra discounts and ultimately, contribute to the formation of customer loyalty (Berman, 2006;Chiu, Hsieh, Li, & Lee, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Chang et al (2013) observed that patients' satisfaction exerts a positive influence on gaining patients loyalty for concerned hospitals. Further, in the hospitality industry, Kim et al (2015) empirically found customer satisfaction and loyalty to be strongly associated. We extend this continuum in this context and posit our next hypothesis:…”
Section: Customer Satisfaction and Customer Loyaltymentioning
confidence: 99%